Rural producer's perspective on the impacts of care in the promotion of animal health and welfare (Research, Society and Development, 2023)
Introduction: This is a study that covers issues of animal health and welfare; in this sense, health care and well-being have been widely debated in society, meeting not only the vital demands of man, but also of the animal, which consists of quality of life Objective: to analyze health care and animal welfare in the Recriar Project, comparing them with the care offered by rural producers on their properties. Material and Methods: This is a qualitative research, which used the participant observer method. This research complied with ethical principles and was submitted to the ethics committee through CAEE 65758922.3.0000.8078 and appears to have been approved. Ten rural producers who were involved in the Recreate Results: Based on the questions raised, it is argued that the project contributes to the reduction of the manpower needed in the properties, since it has a multidisciplinary team dedicated to the care animals, providing adequate food and administering medications correctly when necessary. Considerations: It is concluded that the research carried out on the perception of the rural producer participating in the Recreate Project about the benefits of promoting animal care, health and well-being reveals relevant aspects. Although there are questions from some producers regarding the project's effectiveness in improving animal welfare, it is observed that participation in the project provides significant advantages.